Road Maintenance Administration in Vietnam: Problems and Solutions - Nguyen, Dung; Pham, Thi Tuyet; Do, Van Thuan (International Journal of Sustainable Construction Engineering and Technology, 2022)
Vietnam is in the process of economic transformation which involves lots of requirements for road transport infrastructure development to create a driving force for socio-economic growth and to meet the needs of industrialization and modernization. To have synchronous and sustainable process of developing road infrastructure, maintenance should be paid attention to make the most of the capacity of the existing. Understanding the importance of this work, since 2013, Vietnam Government has issued a relatively sufficient series of policies on road repair and maintenance management. However, there are still shortcomings in road maintenance administration (i.e., discrepancies among legal regulations, challenges in maintenance planning, ineffective selection of contractors, insufficient financing, improper spending, limited introduction of science and technologies), which can hardly be resolved all together at once. The article has studied about the administration and use of the Maintenance Fund and mobilization capital in several countries around the world, at the same time analyzes the status quos of maintenance administration in Viet Nam in the following aspects: management strategies; planning and implementation; policies and regulations on maintenance administration; road quality management; management of maintenance fund, and application of science and technology. Along with the questionnaire in a 3-step approach and SPSS software, the authors have built four groups of influential factors to the road maintenance administration, as well as assessed the level of influence and rationality of each factor. The study then has suggested emergent and practical solutions for more efficient road maintenance management towards sustainable operation of road transport infrastructure.